Alternative diagnosis to heparin-induced thrombocytopenia in two critically ill patients despite a positive PF4/heparin-antibody test. (November 2013) - Hron, Gregor; Knutson, Folke; Thiele, Thomas; Althaus, Karina; Busemann, Christoph; Friesecke, Sigrun; Greinacher, Andreas; Lubenow, Norbert
Abstract Thrombocytopenia can cause diagnostic challenges in patients who have received heparin. Heparin-induced thrombocytopenia (HIT) is often considered in the differential diagnosis, and a positive screening can be mistaken as confirmation of the disorder. We present two patients who both received low-molecular-weight heparin for several days. In the first patient, clinical judgment rejected the suspicion of HIT despite a positive screening assay, and treatment for the alternative diagnosis of post-transfusion purpura was correctly initiated. In the second patient, the inaccurate diagnosis HIT was pursued due to a positive screening assay, while the alternative diagnosis of drug-dependent thrombocytopenia caused by piperacillin/tazobactam was rejected. This resulted in re-exposure to piperacillin/tazobactam which caused a second episode of severe thrombocytopenia. A positive screening assay for platelet factor 4/heparin-antibody should be verified by a functional assay, especially in patients with low pretest probability for HIT.